KINERJA PEGAWAI DILIHAT DARI KEMAMPUAN KERJA, DISIPLIN KERJA DAN TEAM WORK PADA PEGAWAI DINAS KESEHATAN KABUPATEN PEMALANG - Ririn Nurhayati; Sri Suprapti (Serat Acitya, 2019)
This study aims to determine the effect of work ability on the performance of employees of the Pemalang District Health Office. To determine the effect of work discipline on the performance of Pemalang District Health Office employees. To determine the effect of team work on the performance of employees of the Pemalang District Health Office. Based on this, the research is entitled "Analysis of Employee Performance Seen From Work Ability, Work Discipline and Team Work at Pemalang District Health Office Staff".The population in this study were all staff of the Pemalang District Health Office, which numbered 80 people. Sampling using census sampling technique is to determine the number of samples from all existing populations. The sample to be taken in this study is 80 respondents. The data used are primary data by means of a questionnaire. Data analysis using multiple linear regression analysis.Based on the results of the study, the following conclusions can be drawn. There is a positive and significant influence between work ability on the performance of the Pemalang District Health Office staff. With high work ability, the performance of employees will be able to increase. There is a positive and significant influence between work discipline on the performance of employees of the Pemalang District Health Office. With high work discipline, the performance of employees will be able to increase. There is a positive and significant influence between the team work on the performance of the staff of the Pemalang District Health Office. With team work getting higher, the performance of employees will be able to increaseKeyword : Work ability, work discipline, team work and employee performance